Exploitation Of Aquatic Fauna During The Metal Age In Bukit Kamiri, Semporna, Sabah, Malaysia - Bujeng, Velat; A. Albert, Deejay Daxter (Archives of Business Research, 2017)
This article discussed on the analysis of faunal remains from the aquatic environment uncovered from Bukit Kamiri, Semporna, Sabah, Malaysia. Based on the result of archeozoological analysis, the reptile, fish and mollusc remains from the Metal Age cultural layer were consisted of various fish and molluscs species of freshwater, estuarine, mangrove swamp, coastal, coral reef and marine habitats. A range of fishing, hunting and gathering methods were used to obtain the various types of food and resources. Besides their diet, the reptile, fish and mollusc remains also show that it was used multi-purposely as grave goods, based on its association with the finding of human burial.